2022
DOI: 10.4102/sajr.v26i1.2485
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield and accuracy of paediatric image-guided fine needle aspiration biopsy of deep organ tumours

Abstract: Background: Paediatric tumour cytological diagnosis by image-guided fine needle aspiration biopsy (FNAB) with rapid on-site evaluation (ROSE) has not gained wide acceptance despite increasing publications advocating the procedure.Objective: The primary aim was an audit of the diagnostic yield and accuracy of paediatric image-guided FNAB with ROSE at a single institution. Evaluation of safety was a secondary aim.Method: Details of consecutive cases of paediatric image-guided FNAB with ROSE for suspected non-ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…8 Many studies have also shown the high accuracy, sensitivity, specificity, and positive predictive value of FNA, including deep organs, such as soft tissue, bone, and liver. [9][10][11][12][13][14] Moreover, the use of standardized practices can significantly improve tissue collection, especially for organ-specific recommendations of needle selection, the number of needle passes, and the use of multidisciplinary teams, including radiology, pathology, and oncology. 15 The objectives of this study were to evaluate the role of ROSE in clinical trial-associated small-core biopsy adequacy and to identify continuous and/or categorical predictors of adequacy and cumulative survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Many studies have also shown the high accuracy, sensitivity, specificity, and positive predictive value of FNA, including deep organs, such as soft tissue, bone, and liver. [9][10][11][12][13][14] Moreover, the use of standardized practices can significantly improve tissue collection, especially for organ-specific recommendations of needle selection, the number of needle passes, and the use of multidisciplinary teams, including radiology, pathology, and oncology. 15 The objectives of this study were to evaluate the role of ROSE in clinical trial-associated small-core biopsy adequacy and to identify continuous and/or categorical predictors of adequacy and cumulative survival.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well demonstrated that they provide reliable diagnoses comparable to those of cytopathologists as they relate to tissue adequacy 8 . Many studies have also shown the high accuracy, sensitivity, specificity, and positive predictive value of FNA, including deep organs, such as soft tissue, bone, and liver 9–14 . Moreover, the use of standardized practices can significantly improve tissue collection, especially for organ‐specific recommendations of needle selection, the number of needle passes, and the use of multidisciplinary teams, including radiology, pathology, and oncology 15 …”
Section: Introductionmentioning
confidence: 99%
“…First, sampling of biological material should originate from the most representative region of the pathology. This may be secured, for example, by image-guided biopsy [8,9] using ultrasound or other technologies. Second, the preparation of the material should ensure that the most informative features of the pathology will be visually identifiable when viewed under the microscope.…”
Section: Introductionmentioning
confidence: 99%